2016
DOI: 10.1200/jco.2015.62.1276
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Perfusion and Gray Matter Changes Associated With Chemotherapy-Induced Peripheral Neuropathy

Abstract: Purpose To investigate the longitudinal relationship between chemotherapy-induced peripheral neuropathy (CIPN) symptoms (sx) and brain perfusion changes in patients with breast cancer. Interaction of CIPN-sx perfusion effects with known chemotherapy-associated gray matter density decrease was also assessed to elucidate the relationship between CIPN and previously reported cancer treatment–related brain structural changes. Methods Patients with breast cancer treated with (n = 24) or without (n = 23) chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 31 publications
0
47
0
1
Order By: Relevance
“…While the patient-reported sensory symptoms and decreased pin prick sensitivity may suggest that damage to peripheral somatosensory nerves contributed to these deficits, it is unknown whether previously reported cases of taxane toxicity to optic [37,38] and/or motor nerves [39] or the central nervous system [40] were also contributors. As these systems are all integral to postural control and physical function, future research is warranted to elucidate contributors to the functional deficits suggested by this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the patient-reported sensory symptoms and decreased pin prick sensitivity may suggest that damage to peripheral somatosensory nerves contributed to these deficits, it is unknown whether previously reported cases of taxane toxicity to optic [37,38] and/or motor nerves [39] or the central nervous system [40] were also contributors. As these systems are all integral to postural control and physical function, future research is warranted to elucidate contributors to the functional deficits suggested by this study.…”
Section: Discussionmentioning
confidence: 99%
“…The comparatively large changes in balance parameters suggest that tracking patient balance may provide an objective measure to detect changes early in treatment. The utility of including an objective measure in clinical assessments of CIPN is supported by Nudelman et al, who suggested that the changes to cerebral structures associated with developing CIPN may increase the risk of patients to underreport symptoms on patient-reported outcomes [40]. By including an objective measure of patient function, clinicians may be better able to detect CIPN symptoms compared to relying solely on patient-reported measures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been noted that methodological factors pertaining to imaging analyses, such as selection of statistical thresholds, may in part influence the pattern and extent of regional findings when different analytic approaches are used (McDonald and Saykin 2013). We derived our cluster extent threshold empirically taking into account the voxel size used in the structural and functional MRI data, which is equally or more conservative than other imaging studies in cancer survivors (de Ruiter et al 2011; Deprez et al 2014; Stouten-Kemperman et al 2015; Nudelman et al 2016). The validity of our reported findings is further strengthened by the fact that structural and functional differences overlapped or were regionally adjacent, suggesting structural differences may have contributed to functional differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included a self-reported history of prior cancer; substance abuse; and other medical, neurological, and psychiatric risk factors with the potential to affect central or peripheral neurological structure/function [30, 31]. All Ctx+ women were treated with standard doses of chemotherapy agents known to cause CIPN-sx, such as taxanes and platinum compounds.…”
Section: Methodsmentioning
confidence: 99%